Hałasy, które nas nawiedzają. Cisza, żałoba i dźwiękowe abiekty - Brzostek, Dariusz (Zagadnienia Rodzajów Literackich, 2021)
This paper focuses on the problem of silence regarded as an acoustic framework in which uncanny sonic phenomena appear. Some of these haunting noises take the form of sound abject — an unwanted sound of the human body, „neither [sound] subject nor [sound] object”. Borrowing terms from two eminent authors of twentieth-century aesthetics — Julia Kristeva, who proposed the concept of abject, and Pierre Schaeffer, who announced the existence of acousmatic sound objects, I hereby take the liberty of introducing the idea of „sound abject” — an unwanted, uncanny corporeal sound (the sound of the body itself ), uncontrolled by the self and constituting neither a subject nor an object but a sound phantasm that separates from the body and resounds worrisomely. I analyse the cases of sound installation created by Jan Simon as well as the Jamaican dub music production strategies.